Réponses

2014-03-02T14:43:02+01:00
1)   8x-3/4=2x-1/4
8x - 3/4 - 2x = -1/4
6x = -1/4 + 3/4
6x = 2/4
x = (2/4)/6
x = 3

2)   24/7x+1/14=3/28
24/7x = 3/28 - 1/14
24/7x = 3/28 - 2/28
24/7x = 1/28
x = (1/28)/(24/7)
x = 1/96

3)   2x-3/7=5x-7/2

-3/7 = 5x - 7/2 - 2x
-3/7 + 7/2 = 3x
-6/14 + 49/14 = 3x
43/14 = 3x
x = (43/14)/3
x = 43/42
tu es sûr pour le 1)?
Non, c'est toi qui a raison :)
ok ;)
^^
2014-03-02T14:59:48+01:00


1 ) 8 x -(3/4) = 2 x -(1/4)

     8 x - 2 x = -(1/4) + (3/4)

   6 x = 2/4 ou 1/2

    x = (1/2) / 6

   x = (1/2) x (1/6)

x = 1/12


2) (24/7) x + (1/14) = 3/28

   (24/7)x  = (3/28) - (1/14)

(24/7) x = (3/28) - (2/28)

(24/7)x = 1/28

 x = (1/28) / (24/7)

x = (1/28) x (7/24) -----------j'ai simplifié (1/4) x (1/24)

x = 1/96


3)  2x - (3/7) = 5x - (7/2)

    -(3/7) = 5x - 2x-(7/2)

-(3/7) = 3x -(7/2)

-(3/7)+(7/2) = 3x

-(6/14) + (49/14) = 3x

(43/14) = 3x

(43/14) / 3 = x

(43/14) x (1/3) = x

(43/42) = x


voilà

  

je n'ai pas la même réponse pour le 1) que nonoduchablais